L’inconciliabile. Il secolo di Alain Badiou e Pier Paolo Pasolini - Tusa, Giovanbattista (Scenari, 2021)
My paper was originally published in 2016 as an afterword for Badiou’s Italian edition of À la recherche du réel perdu (Fayard, Paris 2015). In this book Badiou devotes a lengthy discussion of «The Ashes of Gramsci», a poem written in 1954 by Pier Paolo Pasolini. Commenting on Pasolini’s poem, Badiou describes the contemporary western world as a world where «there is nothing but diversion. There is nothing but the concern to keep oneself as distant from reality as possible». Something that Pasolini will describe as «replacing life by survival», a non-life, or a pseudo-life «able to do no more than continue the negative work of diversion». In my paper I explore Badiou’s strong relationship with Pasolini’s work for his understanding of the 20th century, which he defined – in the historical seminar that Badiou gave at the Collège International de Philosophie of Paris, later published as Le Siècle – as the century of «the passion for the real».